Design Reduirement of Pasar Besar Malang Through Site Analysis Method - Ade Fitriyanti Ulul Azmi; Vincentius Totok Noerwasito; Ima Defiana (Institut Teknologi Sepuluh Nopember, 2020)
In discussing traditional markets, not a few are found that the market experiences a setback in existence in the community. The decline in the existence of traditional markets, one of which occurred in the Great Market of Malang with the increasing lifestyle of Malang people in harmony with technological sophistication. Pasar Besar Malang has urgency, which is experiencing 3 fires and is increasingly doubting the ability of Pasar Besar Malang to guarantee safety and comfort on the move. In addition to buyers, traders also experienced a decrease in the number due to the uneven distribution of trade transactions that caused traders to continue to suffer losses. Through the site analysis study method and the sense of place approach that is applied to the questionnaire, the potential and the possibility of utilization are explored by producing design requirements. Implementation of design requirements in the form of design aspects that discuss such as optimizing access and circulation through the transition zone. This is done in order to create a quality of space that is comfortable and able to provide sustainability for the existence of Pasar Besar Malang as a provider of needs and public space.